Fisheye piezo polymer detector for scanning optoacoustic angiography of experimental neoplasms - Alexey Kurnikov; Grigory Volkov; Anna Orlova; Andrey Kovalchuk; Yulia Khochenkova; Daniel Razansky; Pavel Subochev (Photoacoustics, 2023)
A number of optoacoustic (or photoacoustic) microscopy and mesoscopy techniques have successfully been employed for non-invasive tumor angiography. However, accurate rendering of tortuous and multidirectional neoplastic vessels is commonly hindered by the limited aperture size, narrow bandwidth and insufficient angular coverage of commercially available ultrasound transducers. We exploited the excellent flexibility and elasticity of a piezo polymer (PVDF) material to devise a fisheye-shape ultrasound detector with a high numerical aperture of 0.9, wide 1–30 MHz detection bandwidth and 27 mm diameter aperture suitable for imaging tumors of various size. We show theoretically and experimentally that the wide detector’s view-angle and bandwidth are paramount for achieving a detailed visualization of the intricate arbitrarily-oriented neovasculature in experimental tumors. The developed approach is shown to be well adapted to the tasks of experimental oncology thus allows to better exploit the angiographic potential of optoacoustics.